THE USE OF NANOMATERIALS IN COSMETIC PRODUCTS ACCORDING TO THE SHARIA PERSPECTIVE (International Seminar on Syariah and Law (INSLA), 2024)
Nanocosmetics is a term that refers to cosmetic products that use nanomaterials or nanotechnology to enhance their performance and quality. However, some nanocosmetic products may contain ingredients that are questionable from an Islamic perspective, such as animal extracts and alcohol. This study aimed to understand the concept of nanocosmetics according to a scientific view and to examine the Islamic ruling on using such products, especially those that involve cosmetic treatments like powder embroidery. A qualitative research methodology was employed, using various sources from websites, books, journals, and articles. The results and discussion section covered the definitions of nanomaterial, cosmetic, and nanocosmetic, as well as the Sharia perspective on animal-based and alcohol-based cosmetic products. The study also analyzed the Sharia perspective on powder embroidery, which is a cosmetic treatment that uses nanomaterials to create semi-permanent makeup. The study found that powder embroidery is permissible if the treatment is done for medical reasons, such as to cover scars or skin diseases, and not to change one’s appearance. However, powder embroidery is prohibited if the treatment poses more harm than benefit to the consumer, such as causing infections, allergies, or pain. The study concluded that nanocosmetic products and treatments should be used with caution and awareness and that consumers should seek reliable and authentic information from Islamic scholars and experts before using them.